Validation of Vitamin C Analysis Method and Evaluation of Antioxidant Activity of Various Plant Extracts From South Kalimantan Using UV-Vis Spectrophotometer - Idris, Muddatstsir; Kasumawati, Fahrina (Program Studi Kimia, Universitas Lambung Mangkurat, 2024)
The UV-Vis spectrophotometer is commonly utilized for sample analysis in practicums, research, and community service. The analysis method employed in these activities must utilize a proven analytical technique to ensure the accuracy, precision, and accountability of the produced results. Hence, one of the aims of this study was to verify the vitamin C analysis technique for its linearity, accuracy (% recovery), precision (% RSD), limit of detection (LOD), and limit of quantitation (LOQ). Additionally, the validated analytical method will be employed to analyze the vitamin C content in pempaken fruit (Durio kutejensis Hassk (Becc.)) and kalangkala fruit (Litsea garciae Vidal). The linearity of a method was assessed by examining the correlation between the concentration (x-axis) and the response (y-axis). Percentage recovery was determined by quantifying the concentration of vitamin C in the sample and subsequently quantifying the concentration of vitamin C in the sample following the addition of a known quantity of a standard solution. The calculation of % RSD involves dividing the standard deviation (SD) by the average level (µg/mL) and then multiplying the result by 100%. LOD was determined by dividing the standard deviation by the slope value . Meanwhile, the determination of LOQ was accomplished by the use of a mathematical formula . South Kalimantan is abundant in medicinal plants, such as pampakin and kalangkala. Hence, another objective of this study was to assess the antioxidant activity of the extracts from these two plants using the DPPH method, employing a UV-Vis Spectrophotometer for analysis. The linearity, detection limit, quantitation limit, accuracy, and precision of the validated vitamin C analysis method were as follows: 0.999, 0.50ppm, 5.02ppm, 99.45-101.48%, and 0.03-1.33%, respectively. A 1.0 g sample of kalangkala and pampakin fruit contained 0.24 mg and 0.13 mg of vitamin C, respectively. The antioxidant activity test revealed that the kalangkala leaf extract exhibited potent antioxidant properties, with the solvents ranked in the following order of efficacy: methanol (IC50=23.03 µg/mL) > ethyl acetate (IC50= 27.16 µg/mL) > methylenechloride (IC50= 27.45 µg /mL) > n-hexane (IC50= 32.01 µg/mL). Pampakin leaves, kalangkala fruit, and pampakin fruit showed the highest antioxidant activity in methanol extract with IC50, respectively 50.29, 48.70, and 45.30 µg/mL. Based on the findings of this study, the vitamin C analysis method utilizing a UV-Vis spectrophotometer passes the validation requirements, and the antioxidant activity of pampakin and kalangkala fruit on DPPH free radicals is most likely attributable to the vitamin C found in these fruits. Meanwhile, extracts of the two plants derived from methanol demonstrated the strongest antioxidant activity when compared to other solvents such as n-hexane, methylene chloride, and ethyl acetate.